Ongoing outbreak of maternal parvovirus B19 infections in Germany since end of 2023: consequence of COVID-19 pandemic? - Jiménez Cruz, J.; Axt-Fliedner, R.; Berg, C.; Faschingbauer, Florian; Kagan, K. O.; Knabl, Julia; Lauten, A.; Lehmann, H.; Stepan, H.; Tavares de Sousa, M.; Verlohren, S.; Germer, U.; et al. (Ultrasound in Obstetrics & Gynecology, 2025)
Objective: To investigate the ongoing parvovirus B19 (B19V) outbreak among pregnant women in Germany and its connection to the coronavirus disease 2019 (COVID-19) pandemic. Methods: This retrospective cohort study analyzed anonymous data regarding serologically confirmed B19V infections during pregnancy between January 2014 and April 2024 across 13 major fetal medicine centers in Germany. We evaluated the yearly frequency of B19V cases, cases that underwent intrauterine transfusion (IUT), cases presenting with hydrops fetalis and cases of intrauterine fetal death (IUFD) related to B19V infection, and stratified these variables by event occurrence < 20 weeks' gestation or ≥ 20 weeks' gestation. Variables were compared across three subperiods: pre COVID-19 pandemic, during the COVID-19 pandemic and post COVID-19 pandemic. Results: Data from 918 pregnant women with confirmed B19V infection revealed a significant B19V outbreak since the end of 2023. The mean ± SD number of annual cases was 57.3 ± 20.7 pre COVID-19, 20.3 ± 13.5 during COVID-19 and surged to 384.8 ± 299.8 post COVID-19 (P < 0.01). Correspondingly, the number of cases in which the fetus underwent IUT increased post COVID-19. The proportion of B19V diagnoses made before 20 weeks' gestation increased from 32.3% pre COVID-19 to 53.2% post COVID-19 (P < 0.001). Conclusions: These results demonstrate an unforeseen increase in B19V infections during pregnancy after the COVID-19 pandemic, with a consequent rise in B19V cases with fetal anemia. The introduced policies during the COVID-19 pandemic reduced the B19V infection rate but likely conditioned the present ongoing upsurge. Counseling, early detection and access to specialized centers performing IUT are essential measures required to address this outbreak. © 2025 The Author(s). Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.
CRIS-Team Scopus Importer:2025-03-28
Keywords: COVID-19 pandemic; fetal anemia; hydrops fetalis; infectious disease in pregnancy; intrauterine transfusion; parvovirus B19